A web-based blood donation system with identification card for blood donor using QR code / Nur Amalia Nainun - Nainun, Nur Amalia (2017)
Currently, the registration for blood donation is done manually which donor have to fill the same registration form every time they make donation. This process discourage lots of possible donor. Beside, this manual system has obvious weaknesses, that it gives load of paper works, manual filing works and data redundancy, apart from requiring lots of space and time to manage the files. The record for blood donation is save in the blood donation record books. Donor face difficulties when they have to bring the record book when they want to make donation. In contrast with the Web Based Blood Donation System for Blood Donor Using QR Code, which is an embedded system that combines a web-based type of system with an identification card function. The card features include the donor details like donor’s name, NRIC blood type, and QR Code. This QR code is printed on the card to store the details of the donor. The QR code is generate from the donor’s NRIC. The purpose of this study is to design and develop a web-based blood donation system with QR Code by using rule-based technique. The method that has been used in this study is incremental model. The language used to design this system is PHP, whilst the language used for the interface is HTML and CSS. phpMyAdmin is used as the database in this system. In the preliminary stage, questionnaires are designed to elicit information to help further research in the study. From this questionnaire the public feedback about the blood donation service are recorded. Based on the questionnaire conducted, it is found that most of the donor prefer to use blood donation card instead of blood donation record book. Beside, computerized system give a clear advantage over a manual system. This system is seen to be able to overcome the problems arising from use of the blood donation record book and manual system. For future work, computerize blood donor qualification questionnaire, donor health record, available donating date notification to donor after three month of previous donation and calendar in donor page will enhance the use of the system.